Hemolytic uremic syndrome and hypertensive crisis post dengue hemorrhagic fever: a case report - Mervin Tri Hadianto; Omega Mellyana (Paediatrica Indonesiana, 2011)
Hemolytic-uremic syndrome (HUS) clinically manifests as acute renal failure, hemolytic anemia and thrombocytopenia. Acute renal failure with oliguria, hypertension, and proteinuria usually develops in affected patients.1,2 In children under 15 years of age, typical HUS occurs at a rate of 0.91 cases per 100,000 population.3 The initial onset of this disease usually happens in children below 3 years of age. Incidence is similar in boys and girls. Seasonal variation occurs, with HUS peaking in the summer and fall. In young children, spontaneous recovery is common. In adults, the probability of recovery is low when HUS is associated with severe hypertension.2